MENGUKUR TINGKAT KEPATUHAN KEPABEANAN PERUSAHAAN EKSPORT DAN IMPORT DI INDONESIA - Syaifullah Syaifullah; Ramdany Ramdany (STIE Muhammadiyah Jakarta, 2020)
This study aims to prove the compliance of export - import companies with customs regulations. Samples were taken from companies conducting export - import activities listed on the Indonesia Stock Exchange in 2012 - 2017. The number of samples was 157 companies. Free variables consist of company size, profitability, liquidity and leverage. While the dependent variable is customs compliance (audit compliance). The results showed the level of company compliance with customs regulations in the moderate level (moderate).